2010
DOI: 10.1007/s00415-010-5683-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in interhemispheric inhibition following successful epilepsy surgery: a TMS study

Abstract: Epileptic foci can influence cortical excitability, brain perfusion and metabolism not only directly in the focus or perifocally, but also in remote areas. Effects of successful epilepsy surgery on cortical networks and changes in excitability have rarely been addressed. We report a study on changes in interhemispheric inhibition following successful surgical removal of an epileptic focus. Eighteen patients (11 females, 7 males, mean age 34.2 years) were enrolled in this transcranial magnetic stimulation (TMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
1
8
0
2
Order By: Relevance
“…Postoperative changes in the contralateral hemisphere were also reported previously, in the form of increased intracortical facilitation (the late part of the short ISI curve) in one study (Kamida et al., ), and reduced intracortical facilitation together with shortening of the cortical silent period (denoting increased cortical excitability) in another (Lappchen et al., ). Another study also found increased interhemispheric inhibition on stimulation of the unaffected hemisphere postoperatively (Lappchen et al., ). Such contradictory findings may be due to sample size; however, they may also be due to the fact that each of these TMS parameters reflects activity in different intracortical circuits.…”
Section: Discussionmentioning
confidence: 87%
“…Postoperative changes in the contralateral hemisphere were also reported previously, in the form of increased intracortical facilitation (the late part of the short ISI curve) in one study (Kamida et al., ), and reduced intracortical facilitation together with shortening of the cortical silent period (denoting increased cortical excitability) in another (Lappchen et al., ). Another study also found increased interhemispheric inhibition on stimulation of the unaffected hemisphere postoperatively (Lappchen et al., ). Such contradictory findings may be due to sample size; however, they may also be due to the fact that each of these TMS parameters reflects activity in different intracortical circuits.…”
Section: Discussionmentioning
confidence: 87%
“…The conditioning stimulus had an intensity of 80% of RMT, and the test stimulus had an intensity of 120% of the RMT of the related side. Paired magnetic stimuli for IHI with ISI of 8 ms and test pulses without conditioning stimulus were applied at rest in a randomized order of 20 test stimuli (10 with and 10 without conditioning stimulus) (Läppchen et al, 2011). New RMT were determined for IHI.…”
Section: Tmsmentioning
confidence: 99%
“…Thus, several of these listed case studies and small case series of refractory epilepsy patients showed significant reductions in seizures when low frequency TMS was applied. Specifically, interhemispheric inhibition in epilepsy patients was explored in one study: 18 patients prior to and after temporal epilepsy surgery were assessed for interhemispheric inhibition by applying TMS (Läppchen et al, 2011). There was significant increase in interhemispheric inhibition tested by applying TMS postoperatively, demonstrating how TMS can be used to assess interhemispheric interaction in epilepsy.…”
Section: Interhemispheric Connectivity In Dbs Studiesmentioning
confidence: 99%
“…In addition, tDCS has been used to induce interhemispheric inhibition similarly to the use of TMS to study interhemispheric inhibition (Läppchen et al, 2011) described in a previous section. Anodal tDCS increased interhemispheric inhibition whereas cathodal tDCS decreased interhemispheric inhibition (Tazoe et al, 2014).…”
Section: Interhemispheric Connectivity In Dbs Studiesmentioning
confidence: 99%